2021
DOI: 10.3389/fcell.2021.737426
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Inhibits Choroidal Neovascularization Through Mitigation of Inflammatory and Angiogenesis Activities

Abstract: Adenosine receptors (AR) are widely expressed in a variety of tissues including the retina and brain. They are involved in adenosine-mediated immune responses underlying the onset and progression of neurodegenerative diseases. The expression of AR has been previously demonstrated in some retinal cells including endothelial cells and retinal pigment epithelial cells, but their expression in the choroid and choroidal cells remains unknown. Caffeine is a widely consumed AR antagonist that can influence inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 75 publications
(111 reference statements)
1
10
0
Order By: Relevance
“…We also demonstrated that caffeine inhibits the migration of retinal and choroidal endothelial cells. [19] Thus, the results of the current study suggesting that the A2A receptor may have altered expression in human eyes with AMD fits well with prior findings. Together these results suggest a potential role for adenosine receptor antagonism in preventing changes associated with AMD.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We also demonstrated that caffeine inhibits the migration of retinal and choroidal endothelial cells. [19] Thus, the results of the current study suggesting that the A2A receptor may have altered expression in human eyes with AMD fits well with prior findings. Together these results suggest a potential role for adenosine receptor antagonism in preventing changes associated with AMD.…”
Section: Discussionsupporting
confidence: 90%
“…We previously showed predominant expression of A1 receptor in mouse microglia and retinal vascular cells. [19] Receptors A2A, A2B, and A3 displayed gene expression within both the retina and choroid. Although A1 receptor expression was significantly lower, the expression of A2A and A3 were significantly higher in the choroid/RPE compared with the retina, as we previously reported in human and mouse tissue samples.…”
Section: Adenosine Receptors Mrna Expression In Retina and Rpe/choroi...mentioning
confidence: 99%
See 2 more Smart Citations
“…IM-HCF cells were cultured in six-well plates at a density of 1.5 × 10 6 cells/well; the day after, cells were stimulated with TGF-β at the concentration of 10 ng/mL for 24 h to induce a fibrotic phenotype. Cells were treated with two different A 2A receptor antagonists, Istradefylline (Tocris Bioscience Bristol, Bristol, UK) and ZM241385 (Tocris Bioscience Bristol, Bristol, UK), for 24 h, at concentrations of 10 µM and 1 µM, respectively, alone or following TGF-β challenge, as previously described [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%